Pengabdian Masyarakat Dalam Meningkatkan Kinerja Keuangan Pada Warung Sayur Cabe Balap Di Desa Cicau Cikarang Pusat Jawa Barat: (Community Engagement in Enhancing Financial Performance at Warung Sayur Cabe Balap Cicau Village Central Cikarang West Java) - Sheila Amartya Tribanowati Warakawiri; Syifa Amelia Putri Hidayat; Nani Hartati (Prodi Tadris IPA Biologi UIN Mataram, 2024)
This study discusses the importance of financial record-keeping in improving the financial performance of SMEs, focusing on Warung Sayur Cabe Balap. It was found that a lack of understanding of financial record-keeping can hinder business growth. Through community service activities, socialization, training, and financial reporting were conducted for the business owner. The aim of these activities is to train the SME in structured financial record-keeping and to differentiate between cash inflows and outflows. The research employed a direct observation method, where the researcher provided face-to-face training over four weeks on the importance of financial record-keeping to the SME. The training included the introduction of financial statements, relevant accounts, and examples of transaction recording to familiarize the business owner. The ultimate goal is for the owner to understand and perform financial record-keeping accurately and efficiently. The results indicate that financial management assistance can help SMEs create income statements, manage cash flows, plan finances, and develop financial strategies. The use of financial management applications can enable SMEs to grow optimally. In conclusion, with this assistance, business owners can easily create income statements, manage cash flows, plan finances, and develop the necessary financial strategies to enhance their business. Additionally, business owners can use financial management applications to automatically and regularly record financial transactions using Microsoft Excel and the Buku Kas application, allowing the business to grow effectively and optimally.